Biocompatible octacalcium phosphate/sodium alginate/silk fibroin composite scaffolds for bone regeneration. (June 2022) - Chen, Jiwen; Wang, Huajun; Wu, Yunjun; Liu, Youjie; Shi, Yiwan; Chen, Changshun; Hou, Huige; Zha, Zhengang; Zheng, Xiaofei; Wu, Tingting
Abstract: The repair of bone defect, especially large bone defect remains as a significant clinical challenge. In the present study, we fabricated a novel scaffold OCP/SA/SF which was a composite of octacalcium phosphate (OCP), sodium alginate (SA) and silk fibroin (SF). The SEM images showed that it was porous sponge-like and the pore sizes were suitable for the ingrowth of cells and facilitated nutritions and fluids exchange. FTIR spectra and XRD showed characteristic absorption peaks of the OCP and SF of the scaffolds. In vitro swelling and degradation showed good water-binding and biodegradable ability of the scaffolds. Compressive stress test showed that the compressive strength of the scaffolds increased gradually as the OCP contents increased. HA deposition onto the surface of the scaffolds was seen by SEM after 14 days of soaking the scaffolds in SBF. The cultivation of mBMSCs on the scaffolds for 1 day and 7 days showed good biocompatibility through CCK8 assay, SEM and CLSM images. Osteogenic differentiation genes detection showed osteogenic genes ALP, OC, COL1 and OPN were all upregulated when mBMSCs and the scaffolds were cocultured for 7 days and 14 days. In conclusion, this kind of scaffolds showed good mechanical, biocompatible and biodegradable properties, and were nontoxic to mBMSCs. It can promote proliferation and osteogenic differentiation of mBMSCs. Accordingly, it might be a promising biomaterial for the clinical application of bone defect. Graphical Abstract: ga1